2017
DOI: 10.3168/jds.2016-12257
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of a commercial footbath product with copper sulfate for the control of digital dermatitis

Abstract: Digital dermatitis (DD) is the most prevalent foot lesion affecting dairy herds worldwide. Its implications include production losses and decreased animal welfare. Footbathing is the most common herd-level prevention strategy for DD. Because many common footbath products have negative environmental and health consequences, replacement products expected to have improved safety but equal efficacy are being developed. Therefore, the aim of this study was to evaluate the efficacy of a new quaternary ammonium-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
(59 reference statements)
1
10
1
Order By: Relevance
“…Other reports of DD prevalence in lactating cattle have focused on M1 and M2 stages only (Somers et al, 2003), different scoring systems (Holzhauer et al, 2006), or specific groups of animals (Capion et al, 2012). Multi-farm footbath trials conducted in Alberta, Canada, have reported prevalence of M1-M4.1 lesions ranging between 15 and 86% (Jacobs et al, 2017;Solano et al, 2017b), similar to this study.…”
Section: Discussionsupporting
confidence: 82%
“…Other reports of DD prevalence in lactating cattle have focused on M1 and M2 stages only (Somers et al, 2003), different scoring systems (Holzhauer et al, 2006), or specific groups of animals (Capion et al, 2012). Multi-farm footbath trials conducted in Alberta, Canada, have reported prevalence of M1-M4.1 lesions ranging between 15 and 86% (Jacobs et al, 2017;Solano et al, 2017b), similar to this study.…”
Section: Discussionsupporting
confidence: 82%
“…We analysed data collected in parallel with the published randomized controlled trial by Jacobs et al [ 14 ]. The IRT measurements and locomotion scores ( LS ) were not analysed before, whereas the M-scores, lower leg cleanliness scores ( CS ), and farm descriptives were used from Jacobs et al [ 14 ]. All methods were approved by the Animal Care Committee (AC13-0055) of the University of Calgary.…”
Section: Methodsmentioning
confidence: 99%
“…Each farm was located in Alberta, Canada, and data were collected from May to August 2013 on the first four farms and in November 2013 on the fifth farm. The routine treatment and hoof trimming schedule was maintained for all farms over the course of the study [ 14 ]. We refer the reader to Jacobs et al [ 14 ] for details on the footbathing practices for lactating cows.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations